Designation of a neotype for the Australian robber fly Ommatius dimidiatus Macquart, a new senior synonym of Ommatius pilosus White and Ommatius levis White (Diptera: Asilidae: Ommatiinae) - Daniels, Greg (Zootaxa, 2018)
The holotype of Ommatius dimidiatus Macquart is confirmed as being lost and two specimens labeled as syntypes in the Muséum National d’Histoire Naturelle, Paris are considered not to have any type status. In accordance with Article 75 and complying with the qualifying conditions of Article 75.3 of the International Code of Zoological Nomenclature, a Tasmanian specimen of O. pilosus White, the only Ommatius Wiedemann species known to occur in Tasmania, is designated as a neotype of O. dimidiatus. Ommatius pilosus and O. levis White are confirmed as junior synonyms of O. dimidiatus.